PEMILIHAN KELURAHAN CALON LOKASI TPU DI JAKARTA - Kevin Yosua Caisario; H W Wiranegara; Herika Muhamad Taki (Universitas Trisakti, 2022)
DKI Jakarta experienced a public cemetery (TPU) land crisis during covid-19 which caused 3 (three) overcapacity TPU lands (DKI Jakarta Provincial Government, 2021). The need for TPU is increasing, causing problems such as a shortage of grave land. In overcoming this problem, a plan for selecting a new TPU location is needed, considering the land crisis can be minimized and the community's need for public burial places is still met. The DKI Jakarta Spatial Planning & Zoning Pattern designates 97 sub-districts to become TPU land developments. In choosing the location of the new TPU, a structured research method is needed, so that among these 97 sub-districts the best location can be chosen, in selecting the right location by using the map overlay analysis method (arcGIS). The stages of selecting the location of the new TPU use criteria, namely, the use of vacant land, the slope of the slope, the radius of the settlement which will be tested simultaneously in 97 urban villages. The results of this study selected 3 sub-districts to be the location of the new TPU, namely Rorotan, Grinding and Rawa Terate Villages. This selected sub-district has an area of +10 ha of vacant land, has a minimum radius of 500m from the settlement and a suitable slope